SONIC REBELLIONS sound and social justice. - Canton, Wanda ([S.l.] : FOCAL, 2024)
"Sonic Rebellions combines theory and practice to consider contemporary uses of sound in the context of politics, philosophy, and protest, by exploring the relationship between sound and social justice, with particular attention to sonic methodologies not necessarily conceptualised or practiced in traditional understandings of activism. An edited collection written by artists, academics, and activists, many authors have multidimensional experiences as practitioners themselves, and readers will benefit from never before published doctoral and community projects, and innovative, audio-based interpretations of social issues today. With chapters covering the use of soundscapes, rap, theatre, social media, protest, and song, in application to contemporary socio-political issues such as gentrification, neoliberalism, criminalisation, democracy, and migrant rights. Sonic Rebellions looks to encourage readers to become, or consider, how they are Sonic Rebels themselves, by developing their own practices and reflections in tandem to continue the conversation as to how sound permeates our socio-political lives. This is an essential resource for those interested in how sound can change the world, including undergraduates and postgraduates from across the social sciences and humanities, scholars and instructors of sound studies and sound production, as well as activists, artists, and community organisers"--
Keywords: Music -- Political aspects; Social justice; Protest movements; MUSIC / Genres & Styles / Rap & Hip Hop; POLITICAL SCIENCE / General